Shock Energy Conversion from Translation to Rotation - Hongyuan Zhou; Xiaojuan Wang; Xuejian Zhang (Shock and Vibration)
To protect structures from short duration shock load in various engineering applications, a novel energy conversion mechanism with concept design is proposed. Different from conventional methods with cellular solid/structure dissipating input translational kinetic energy to plastic strain energy with large compressive deformation, the proposed approach converts part of incident translational kinetic energy to rotational kinetic energy, which is not detrimental to the protected structure. The mechanism of energy conversion is analyzed and formulated, with key factors governing the conversion efficiency identified and discussed, which sheds light on alternative approach for short duration load mitigation.